Emergence of corporate political activities in the guise of social responsibility: dispatches from a developing economy. Issue 5 (21st January 2021) - Siddiqui, Javed; Mehjabeen, Melita; Stapleton, Pamela
Abstract : Purpose: The objective of this paper is to investigate the emergence of corporate political activities (CPAs) in the form of social responsibility in the banking sector in Bangladesh. The use of institutional logics allows the authors to explore not only the motivations underlying this sudden shift in corporate approach towards corporate social reporting (CSR) disclosure but also to investigate whether a logical plurality exists in this new approach. Design/methodology/approach: The analysis is based on 21 in-depth interviews with policymakers, regulatory bodies and top management and members of boards of directors in the banking sector. Findings: The findings of this study are both consistent with and different to those of Uddin et al. (2018). While their findings show that Bangladeshi companies engage in CSR activities primarily to demonstrate their allegiance with the ruling political regime driven by notions of traditionalism, this study's findings show the existence of a logical pluralism across industries in the manner they engage with CSR activities and disclosures. In addition to the dominant market logic, the authors also find the co-existence of community and family logics shaping the nature of CSR disclosures made by banking companies in Bangladesh. Originality/value: The authors contribute to the accounting and management literature by providing first-hand evidence of the motivations underlying the emergence of CPAs in the context of a developing country. The adoption of an alternative theoretical framework allows the authors to identify the multiple logics that dictate corporate attitude towards CSR engagement and disclosure.